VICIOUS CIRCULATION OF WATER DEFICIENCY AND WATER POLLUTION – “CANCER” OF THE RIVERS IN THE NORTH OF CHINA. - Yang Liankang; Pan Yuntang; Yang Yi (Sociedade & Natureza)
The North of China belongs to the basin of the Tarim River ,the Heihe River , the Yellow River , the Huaihe River ,the Haihe River ,the Liaohe River , the Heilongjiang River and other shorter rivers and other indraft areas. The total area of all river basin is about 3,200,000 sq. km., exceeds 3/5 of area of land of 13 provinces , municipalities and autonomous regions of the North of China (5, 220,000 sq. km. ).Follow the growth of the economy and the population, lacking of water in the rivers of the northern China is serious,. Since the sixties and seventies of previous century, the blanking has taken place successively in numerous rivers, brought serious influence on the development of the economic, made the society to shake. Afterwards, through certain effort, although the blanking phenomenon is alleviated for the past several years, but the water quality of manyrivers has sharply worsened and was dropped to V, bad V grade in the numerous sections, fromthe situation that the water quality in a great part sections in the main stream was still rather good for past more than 20 years ago. It has become the first killer, influencing the life of river.Therefore, we must summarize the experiences on that the rivers of the northern China, especially the most influential Yellow River, have gone from blanking to resuming flow, we also must control the pollution and proportionate the development of the society and theeconomic, with the water yield and the water quality. These affair have already become task of top priority!